Experimental model of opisthorchiasis in hamsters (Mesocricetus auratus) - G. A. Maksimova; N. A. Zhukova; Ye. V. Kashina; M. N. Lvova; A. V. Katokhin; T. G. Tolstikova; L. M. Ogorodova; I. P. Kaminsky; A. E. Sazonov; V. A. Mordvinov (Бюллетень сибирской медицины)
An experimental model of opisthorchiasis on hamsters (Mesocricetus auratus) was obtained, the DNA O. felineus was investigation by molecular methods, histological study of the liver of infected hamsters was carried. Found that the PCR system can detect O. felineus, and does not give false positive results in terms of C. sinensis, O. viverrini, Metorchis bills. Infection leads to marked changes in the liver, which are characterized by specific histological.